2011
DOI: 10.1159/000329388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enamel Defects on Early Caries Development in Preschool Children

Abstract: Quantitative defects of the enamel are considered risk factors for caries development at the cavitated level. Since caries risk assessment and control should be implemented as early as possible in order to prevent operative treatment, it seemed interesting to investigate the relationship between enamel defects and caries development in the stages of progression that precede cavitation. The impact of enamel defects and selected child-mother indicators on early caries development was investigated in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
2
20
0
6
Order By: Relevance
“…A certain percentage of teeth may present qualitative and/or quantitative hypomineralization such as non-fluorotic opacities, fluorotic opacities or hypoplasia. Non-fluorotic opacities and fluorotic opacities are not associated with an increased risk of caries development [Carvalho et al, 2011]. Hypoplasia may cause concerns regarding the risk of caries, tooth sensitivity, the placing of restorations and esthetics; however, a large population-based study showed that the prevalence of molar-incisor hypomineralisation in the permanent dentition was only 8.7% at child level and 5.4% at tooth level [Elfrink et al, 2012].…”
Section: What Is the Underlying Rationale For The Concept Of Incomplementioning
confidence: 99%
“…A certain percentage of teeth may present qualitative and/or quantitative hypomineralization such as non-fluorotic opacities, fluorotic opacities or hypoplasia. Non-fluorotic opacities and fluorotic opacities are not associated with an increased risk of caries development [Carvalho et al, 2011]. Hypoplasia may cause concerns regarding the risk of caries, tooth sensitivity, the placing of restorations and esthetics; however, a large population-based study showed that the prevalence of molar-incisor hypomineralisation in the permanent dentition was only 8.7% at child level and 5.4% at tooth level [Elfrink et al, 2012].…”
Section: What Is the Underlying Rationale For The Concept Of Incomplementioning
confidence: 99%
“…13 Thus, diagnosing and understanding the factors associated with DDE may contribute toward the prevention or minimization of adverse outcomes stemming from such defects. 6,14 The present study was designed to evaluate associations between developmental defects of enamel (DDE) in the primary dentition and aspects related to mothers and preschoolers in the city of Diamantina, Brazil.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Estudos relataram prevalências que podem variar de 23,9% a 90,4% na dentição decídua 2,5,8,23 e de 52% a 92,1% na permanente 4,[9][10][11] . Os fatores que a desencadeiam estão relacionados principalmente a injúrias durante o desenvolvimento da estrutura dental 1 .…”
Section: Discussionunclassified
“…Em crianças com dentição permanente, a frequência da presença de defeitos de esmalte foi observada em estudos que variaram de 52% 3 a 92,1% 4,[9][10][11] .…”
Section: Prevalênciaunclassified
See 1 more Smart Citation